2018
DOI: 10.18632/oncotarget.24581
|View full text |Cite
|
Sign up to set email alerts
|

Selective lysis of breast carcinomas by simultaneous stimulation of sodium channels and blockade of sodium pumps

Abstract: Sodium influx through voltage-gated sodium channels (VGSCs) coupled with balanced removal of sodium ions via Na+, K+-ATPase is a major determinant of cellular homeostasis and intracellular ionic concentration. Interestingly, many metastatic carcinomas express high levels of these channels. We hypothesized that if excess VGSCs are activated and Na+, K+-ATPase is simultaneously blocked, the intracellular Na+ concentration should increase, resulting in water movement into the cell, causing swelling and lytic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…The results of the present study are in vitro and in vivo evidence that support our earlier observation that targeted osmotic lysis, the simultaneous stimulation of VGSCs and Na + , K + -ATPase blockade, is able to kill highly malignant MDA-MB-231 human and 4T1 mouse breast cancer cells while preserving similarly treated normal breast cells [17]. In the in vitro experiments, the lysis of the cancer cells was dependent upon the intensity of the PMF, with greater than 95% of the digoxin treated cancer cells lysing within 15 min, with as little as 80 mT PMF.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of the present study are in vitro and in vivo evidence that support our earlier observation that targeted osmotic lysis, the simultaneous stimulation of VGSCs and Na + , K + -ATPase blockade, is able to kill highly malignant MDA-MB-231 human and 4T1 mouse breast cancer cells while preserving similarly treated normal breast cells [17]. In the in vitro experiments, the lysis of the cancer cells was dependent upon the intensity of the PMF, with greater than 95% of the digoxin treated cancer cells lysing within 15 min, with as little as 80 mT PMF.…”
Section: Discussionsupporting
confidence: 90%
“…The cells of normal tissues have only a fraction of the number of VGSCs compared to highly malignant cancer cells. Consequently, less Na + and thus less water enters the cells, and they do not lyse [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, viral delivery of Na + channels would need to be precisely targeted to neoplastic cells in order for this method to be of use. In a different study, targeted osmotic lysis of VGSC-expressing tumours in mice was demonstrated by systemic administration of the Na + /K + ATPase-inhibiting cardiac glycoside ouabain in conjunction with electrical pulses to open VGSCs, leading to cytotoxic influx of Na + into tumour cells (234). Blocking the Na + efflux activity of Na + /K + ATPase with cardiac glycosides has the added advantage of decreasing inflammation and increasing specific anti-tumour immunity (235).…”
Section: Therapeutic Potential Of Manipulating Na + Levelsmentioning
confidence: 99%